2019
DOI: 10.1249/mss.0000000000002004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Shoe and Surface Stiffness on Lower Limb Tendon Strain in Jumping

Abstract: Background Tendinopathies are painful overuse injuries observed in athletes participating in jumping sports. These injuries are heavily dependent on the resulting strain from the applied mechanical load. Therefore, mechanisms to reduce tendon strain may represent a primary prevention strategy to reduce the incidence of tendinopathy. Purpose The purpose of this study was to examine the effect of shoe and surface stiffness on Achilles and patellar tendon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 29 publications
2
23
0
Order By: Relevance
“…In accordance with recent studies on both indoor and outdoor sport surfaces ( Malisoux et al, 2017 ; Firminger et al, 2019 ; Hatfield et al, 2019 ), jump height was not affected by the type of surface during CMJs. A recent study reported no difference between two different natural turf, an artificial turf, and a force plate ( Hatfield et al, 2019 ) during vertical jumping.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In accordance with recent studies on both indoor and outdoor sport surfaces ( Malisoux et al, 2017 ; Firminger et al, 2019 ; Hatfield et al, 2019 ), jump height was not affected by the type of surface during CMJs. A recent study reported no difference between two different natural turf, an artificial turf, and a force plate ( Hatfield et al, 2019 ) during vertical jumping.…”
Section: Discussionsupporting
confidence: 92%
“…During terrestrial locomotion, the surface/substrate is loaded under the body weight and can act like as an additional spring in series affecting movement efficiency ( Bosco et al, 1997 ; Ferris and Farley, 1997 ; Kerdok et al, 2002 ), intrinsic stability ( Daley and Biewener, 2006 ), energy dissipation ( Hollville et al, 2019 ), and/or performance ( McMahon and Greene, 1979 ; Arampatzis et al, 2004 ; Reynaga et al, 2019 ). However, it seems that in humans, varying common indoor and outdoor sports surfaces do not improve or impair maximal jumping and sprinting performance ( Stafilidis and Arampatzis, 2007 ; Malisoux et al, 2017 ; Firminger et al, 2019 ; Hatfield et al, 2019 ). The main reason is probably due to the low contribution of these standardized sports surfaces to the total mechanical work performed by the human body during maximal motor tasks ( Arampatzis et al, 2004 ; Stafilidis and Arampatzis, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A dynamometry and ultrasound session [30] was performed immediately before the biomechanical testing to estimate the moment arm of the sMTU (MA sMTU ; i.e. Achilles tendon moment arm).…”
Section: Dynamometry and Ultrasound Testingmentioning
confidence: 99%
“…Mechanical work performed by the GM fascicles was calculated as the integral of fascicle force and fascicle length change over the entire stance phase. Achilles tendon force was estimated based on a previously described musculoskeletal model 18 , 50 , 51 . For this, the sagittal plane ankle joint moment was divided by the AT moment arm.…”
Section: Methodsmentioning
confidence: 99%